The Semantic Analysis of Polysemy Concepts in Avengers End Game (2019) - Agustri Agustri; Aztri Dera Nalurytha (Cinematology: Journal Anthology of Film and Television Studies, 2022)
This study uses a descriptive qualitative method with data processing techniques, a direct viewing mode of the film, and the available English subtitles. The main objective of this study is to analyze what words contain equivalence (Polysemy) in the dialogue utterances in the Avengers: End Game movie. Moreover, after a lengthy analysis, it was found that at least eleven polysemies have different denotative meanings, connotations, uses, and functions. What makes this research very important and different from others is that it can provide a broader view for us to understand word variations that have many meanings, functions, and uses more than the word order itself.